Pengaruh Brand Image, Brand Reputation, dan Perceived Quality Terhadap Purchase Intention: Studi Empiris Pada Produk ECO-Friendly Ritel Modern - Zusrony, Edwin; Sulistyowati, Pemilia; Kusumaningtyas, Dhevi Dadi; Manalu, Gibson; Jaelani, Jaelani; Madyoningrum, Asri Winanti; Kustami, Endang (JURNAL ILMIAH EDUNOMIKA, 2024)
Eco-friendly is an environmentally friendly product or behavior that has minimal impact on the environment. This research aims to determine and assess the impact of brand image, brand reputation and perceived quality variables on the dependent variable, namely purchase intention. The research uses a quantitative approach method. The research sample was 100 respondents taken using a non-random sampling technique with a purposive sampling method. Data was collected using a questionnaire and measured using Likert scale parameters. The data analysis technique uses multiple linear regression and is processed using SmartPLS 4.0 software. The research results show that the variables brand image, brand reputation and perceived quality have a significant influence on the purchase intention variable for ECO-Friendly products in modern retail stores.